2015
DOI: 10.1123/apaq.2013-0067
|View full text |Cite
|
Sign up to set email alerts
|

“We Can Talk While We’re Walking”: Seeking the Views of Adults With Intellectual Disability to Inform a Walking and Social-Support Program

Abstract: To better understand how physical activity programs may contribute to improved health and social-support outcomes for people with intellectual disability, the authors conducted semistructured interviews with 11 people with intellectual disability and community-based volunteers in Brisbane, Australia. Three broad themes emerged: individual factors that generally facilitated activity, external factors that posed barriers to participation, and broader normative factors that directed participation. A key reflectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 17 publications
2
32
0
Order By: Relevance
“…Practically, building befriending relationships around shared activities and interests is one potential method for developing leisure–befriending relationships to provide a more novel experience (Anderson & Kress, ; Brooker et al, ; Snow, ; Wilson et al, ); specific roles are more clearly defined, and adults with learning disabilities would be actively engaged in generating a social identity as part of a particular group or social activity alongside volunteers and fellow participants (Heslop, ). How “friendly” befriending relationships are is largely a matter of how equitably power is shared between participants.…”
Section: Discussionmentioning
confidence: 99%
“…Practically, building befriending relationships around shared activities and interests is one potential method for developing leisure–befriending relationships to provide a more novel experience (Anderson & Kress, ; Brooker et al, ; Snow, ; Wilson et al, ); specific roles are more clearly defined, and adults with learning disabilities would be actively engaged in generating a social identity as part of a particular group or social activity alongside volunteers and fellow participants (Heslop, ). How “friendly” befriending relationships are is largely a matter of how equitably power is shared between participants.…”
Section: Discussionmentioning
confidence: 99%
“…Full facilitators were social interaction and being rewarded for participation in physical activities. Twelve studies noted that social engagement with peers, friends, or a team encouraged physical activity in people with ID (Barr & Shields, 2011;Brooker et al, 2015;Dixon-Ibarra, Driver, Vanderbom, & Humphries, 2016;Downs et al, 2014;Downs, Boddy, Knowles, Fairclough, & Stratton, 2013;Frey, Buchanan, & Rosser Sandt, 2005;Mahy, Shields, Taylor, & Dodd, 2010;Menear, 2007;Temple & Stanish, 2011;Temple & Walkley, 2007;Tsai & Fung, 2009;van Schijndel-Speet, Evenhuis, van Wijck, van Empelen, & Echteld, 2014). In six studies (25%), being praised or rewarded was described as having a facilitating effect (Barr & Shields, 2011;Dixon-Ibarra et al, 2016;Frey et al, 2005;Mahy et al, 2010;Temple & Walkley, 2007;van Schijndel-Speet et al, 2014).…”
Section: Personal Barriers To and Facilitators Of Physical Activitymentioning
confidence: 99%
“…This experience is consistent with the self-esteem mechanism described in Chapter 2 where an individual's beliefs about their competence and abilities influences their health (Thoits, 2011). In contrast, people with intellectual disability report enjoying the connections and interactions they have with others while engaging in some physical activities (belonging and companionship mechanism) (Brooker, Mutch, et al, 2015;Dixon-Ibarra et al, 2016;Temple & Walkley, 2007).…”
Section: Physical Activity and Social Supportsupporting
confidence: 79%
“…Temple and Walkley (2007), in their focus groups with people with intellectual disability and their supports, found individuals enjoyed the social opportunities being active provided. Brooker, Mutch, et al (2015) and Dixon-Ibarra et al (2016) reported people with intellectual disability found the opportunity to interact and make connections with others through physical activity was a facilitator to being active. In addition to the enabling effect social support can have on physical activity, lack of social support can act as a barrier to being active.…”
Section: Factors Shaping Participation and Engagement In Physical Actmentioning
confidence: 99%
See 1 more Smart Citation